It ends with us [videorecording (DVD)] - Baldoni, Justin, 1984-; Hall, Christy; Lively, Blake; Slate, Jenny, 1982-; Minhaj, Hasan, 1985-; McKidd, Kevin; Morton, Amy; Neustaedter, Alex, 1998-; Ferrer, Isabela; Sklenar, Brandon, 1990-; Simonsen, Rob, 1978-; Blickenstaff, Duncan; et al. (Sony Pictures Home Entertainment, 2024)
It Ends With Us, the first Colleen Hoover novel adapted for the big screen, tells the story of Lily Bloom, a woman who overcomes a traumatic childhood to embark on a new life in Boston and chase a lifelong dream of opening her own business. A chance meeting with charming neurosurgeon Ryle Kincaid sparks an intense connection, but as the two fall deeply in love, Lily begins to see sides of Ryle that remind her of her parents' relationship. When Lily's first love, Atlas Corrigan, suddenly reenters her life, her relationship with Ryle is upended, and Lily realizes she must learn to rely on her own strength to make an impossible choice for her future.